A Class Act: An Illustrated History of the Labour Movement in Newfoundland and Labrador - Cherwinski, W. J. C. (Walter Joseph Carl) (Labour / Le Travail, 1988)
This article reviews the book, "A Class Act: An Illustrated History of the Labour Movement in Newfoundland and Labrador," by Bill Gillespie.

Joseph Hugh Tuck, 1929-86: A Personal Tribute - Cherwinski, W. J. C. (Walter Joseph Carl) (Labour / Le Travail, 1987)
Pays homage to the life and work of Hugh Tuck, who taught labour history at Memorial University. Includes a list of significant publications and a photo.
Keywords: Joseph Hugh; TUCK

A Flannel Shirt and Liberty: British Emigrant Gentlewomen in the Canadian West, 1880-1914 - Cherwinski, W. J. C. (Walter Joseph Carl) (Labour / Le Travail, 1984)
This article reviews the book, "A Flannel Shirt and Liberty: British Emigrant Gentlewomen in the Canadian West, 1880-1914", edited by Susan Jackel.

Gentlemen Emigrants: From the British Public Schools to the Canadian Frontier - Cherwinski, W. J. C. (Walter Joseph Carl) (Labour / Le Travail, 1983)
This article reviews the book, "Gentlemen Emigrants: From the British Public Schools to the Canadian Frontier," by Patrick A. Dunae.

Alberta Labour: A Heritage Untold - Cherwinski, W. J. C. (Walter Joseph Carl) (Labour / Le Travail, 1981)
This article reviews the book, "Alberta Labour: A Heritage Untold," by Warren Caragata.

The Incredible Harvest Excursion of 1908 - Cherwinski, W. J. C. (Walter Joseph Carl) (Labour / Le Travail, 1980)
To satisfy the continuing need for agricultural labour in western Canada, especially at harvest time, the CPR after 1890 ran cheap harvest excursions from Eastern and central Canada each August and September. Accordingly, to insure an adequate supply of workers and potential settlers the railway companies, together with the federal and provincial governments, created an image of the prairies as a land of opportunity offering plentiful jobs at high wages. Owing to a variety of factors, however, unprecedented numbers responded to the 1908 appeal causing unexpected problems for all concerned. Some of those in the Maritime contingent were particularly troublesome as, bored and thirsty, they went on a rampage which touched most of the communities on the Main Line from Chalk River to Winnipeg. Once in the West distribution problems plagued all the excursionists with the result that places like Winnipeg, Moose Jaw, and Regina had too many harvesters on hand, while other places faced shortages. Consequently, numerous men wandered about aimlessly looking for work and often were forced to accept alternate employment at substantially less money than they had expected. The result was that the image of the West as capable of satisfying all those who went there in search of work was temporarily tarnished.

Lectures in Canadian Labour and Working-Class History - Committee on Canadian Labour History; Cherwinski, W. J. C. (Walter Joseph Carl); Kealey, Gregory S. (Past CCLH Publications, 1985)
In 1983 and 1984 the Canadian Studies Program of the Secretary of State funded four lecture series at Canadian universities on the history of the Canadian working class. This volume presents many of the lectures in a published version. Ranging from east to west and covering two centuries of Canadian labour history, the volume includes a selection of essays by some of Canada's leading social historians including Michael Cross, David Frank, Ross McCormack, Bryan Palmer and Joy Parr. Outstanding participants in the making of Canadian labour history Eugene Forsey and H. Landon Ladd have also contributed. Directed at a popular audience these fourteen lectures provide a major survey of Canada's labour past. --Publisher's description
Keywords: Canada; History; Labor; Labor Unions; Labor movement; Working class